Ray's Salt Water Guide No. 2 : Map - Lower Chesapeake Bay and Patuxent River (1957) - Hugh D. Ray (1957)
Shows Chesapeake Bay from Pt. Lookout to Cove Point. Also Patuxent River. Shows fish types and lures.